Mineral Waste Into Alkali-Activated Pavements (7th International Conference on Technologies & Business Models for Circular Economy: Conference Proceedings, 2025)
The study highlights the pressing need to recycle mineral waste to mitigate resource depletion and environmental damage. It focuses on creating sustainable pavement slabs through alkali activation, using a variety of waste materials such as bio-ash, local slags and mineral wool. Through extensive testing of different mix designs, the optimal mixture was identified: bio-ash, ladle slag, and metakaolin, activated with sodium silicate. This combination demonstrated good mechanical properties and showed low concentrations of toxic elements in leaching tests, confirming environmental safety. The research also prioritized energy efficiency, with the curing process conducted at room temperature and demolding after just one day. A test field at Termit d.d. was established to assess the practical application and potential for commercial use of these innovative paving materials, aiming to support a circular economy by extending the lifecycle of resources.